PENGARUH EFIKASI DIRI SIKAP KEWIRAUSAHAAN DAN PERAN ORANG TUA TERHADAP KESIAPAN BERWIRAUSAHA MAHASISWA SEMESTER VI DAN VIII PRODI PENDIDIKAN EKONOMI UNIVERSITAS BHINNEKA PGRI TULUNGAGUNG - Anatasya Febrianti; Hari Subiyantoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The unemployment problem in Indonesia, especially among college graduates, demands a real solution, one of which is through the development of an entrepreneurial spirit. Students are required not only to be ready for work but also to be able to create their own job opportunities. However, the low entrepreneurial readiness of students and the relatively small proportion of young entrepreneurs are the causes of the increasing number of unemployed. This study aims to analyze the influence of self-efficacy, entrepreneurial attitudes, and parental roles on the entrepreneurial readiness of sixth and eighth semester students of the Economics Education Study Program, Bhinneka PGRI University. The approach used is quantitative with a survey method through the distribution of closed questionnaires to 113 students as respondents. The data analysis technique uses multiple linear regression with the help of SPSS software version 25. The results of the study indicate that partially, self-efficacy, entrepreneurial attitudes, and parental roles have a positive and significant effect on students' entrepreneurial readiness, evidenced by the significance value of each <0.05. Simultaneously, the three independent variables also show a significant influence on entrepreneurial readiness, with a significance value of 0.000. The r square value of 0.450 indicates that 45% of the variation in students' entrepreneurial readiness can be explained by these three variables, while the remaining 55% is influenced by other factors outside this research model.